2017
DOI: 10.1021/acs.jpclett.7b01177
|View full text |Cite
|
Sign up to set email alerts
|

Structural Transformations in Two-Dimensional Transition-Metal Dichalcogenide MoS2 under an Electron Beam: Insights from First-Principles Calculations

Abstract: The polymorphism of two-dimensional (2D) transition-metal dichalcogenides (TMDs) and different electronic properties of the polymorphs make TMDs particularly promising materials in the context of applications in electronics. Recently, local transformations from the semiconducting trigonal prismatic H phase to the metallic octahedral T phase in 2D MoS have been induced by electron irradiation [ Nat. Nanotech. 2014 , 9 , 391 ], but the mechanism of the transformations remains elusive. Using density functional th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 52 publications
4
72
0
1
Order By: Relevance
“…The well-known phase-stability competition between the 2H and 1T′ types in transition metal dichalcogenides (TMDs) has been studied extensively using DFT. Several possible mechanisms for the 1T′phase stabilization in the disulfide, including growth-related factors such as the presence of point defects and residual strain, have been elucidated through DFT calculations 19 . Phase-stability analysis for the entire group -IV metal dichalcogenide family 20 revealed that the 1T′ phases are generally more stable for ditellurides.…”
Section: First-principles Calculationsmentioning
confidence: 99%
“…The well-known phase-stability competition between the 2H and 1T′ types in transition metal dichalcogenides (TMDs) has been studied extensively using DFT. Several possible mechanisms for the 1T′phase stabilization in the disulfide, including growth-related factors such as the presence of point defects and residual strain, have been elucidated through DFT calculations 19 . Phase-stability analysis for the entire group -IV metal dichalcogenide family 20 revealed that the 1T′ phases are generally more stable for ditellurides.…”
Section: First-principles Calculationsmentioning
confidence: 99%
“…Apart from the relatively complex substrate design, physical collision can also render target considerable strain to induce phase transition . Recently, a facile Ar plasma method has been proposed to the trigger phase transition between 2H–1T′ in monolayer MoS 2 .…”
Section: Strategies On Triggering Phase Transition In Tmdsmentioning
confidence: 99%
“…Phase or structural transformation has been demonstrated by electron beam irradiation [42,43], laser beam [44] and electrostatic [45] methods. First principle calculations have also shown that the combination of strain, vacancies, and electronic excitations created by an electron beam can lead to a phase transition [46]. The structure transformation induced by an Ar + ion beam merits further investigation into its mechanism and implications on physical, chemical and electrical properties.…”
Section: Cross-sectional Stem Analysis Of Altered Mosmentioning
confidence: 99%